The importance of the ecology of infectious diseases in the context of Chytridiomycosis and COVID-19 - Koichi Goka (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2023)
Pathogenic microorganisms and viruses are components of ecosystems. They have constructed endemic interrelationships with specific host species throughout the history of coevolution The spillover of pathogens from natural habitats into other areas causes encounters between the pathogens and new hosts that have never evolved immunity or resistance. The result is a rapid spread of "Emerging Infectious Disease" (EID). During the acceleration of globalization, humans and societies have come to be the targets of infectious diseases caused by pathogens that have emerged from natural habitats. In the past few years, the newest EID, SARS-CoV-2, has spread throughout the world and has caused serious harm to human health and welfare. With the growing social concern about the risks of the EID pandemic, there has been discussion that the destruction of biodiversity and environmental changes are closely related to the EID pandemic. There is a need to rethink the importance of conserving biodiversity if humans are to control the risk of pathogenic viruses and live in harmony with them.